MODELLING URBAN GREEN SPACE PROVISION BASED ON LAND USE PROJECTION CHANGES IN DKI JAKARTA PROVINCE - Gerald Marpaung, Samuel
The concept of a Green City emerged against the background of rapid urban growth and resulted in urban problems such as the reduced area of green open space and the phenomenon of climate change (Ernawi, 2012). DKI Jakarta Province, as a province that targets the provision of 30% green open space, consisting of 10% public green open space and 20% private green open space is experiencing challenges in meeting the needs of urban green space. The phenomenon of higher green open space land cover changes, lower water catchment areas, and the emergence of open land that has not been properly utilized by the government and the community are the problems that underlie the need for the provision of green open space in DKI Jakarta. (Bappeda DKI Jakarta Province, 2016). The transformation of the Greater Jakarta area is driven primarily by the expansion of economic activity which is manifested in the construction of industrial complexes and satellite cities. This affects the spatial expansion of mixed land use that occurs on the outskirts of Jakarta (Rustiadi and Panuju, 2002). Based on this, an analysis that describes the land change process in DKI Jakarta is needed in order to estimate the provision of green open space to meet the needs of urban green space. This research was conducted to identify the potential for providing green open space in order to assist policy makers in prioritizing land that has the potential to be maintained or developed as green open space. This study area is the land area of DKI Jakarta Province. This research was conducted using the Cellular Automata method with the driving factors for land use in the form of biophysical, accessibility, socio-economic, infrastructure, neighbourhood, and spatial policies to limit land use change. The results of the research show that the suburbs of DKI Jakarta are predicted to experience land conversion, even though they have a high land suitability value for green open space. Then the factors that drive the change in green open space are related to the percentage of green space provision and natural conditions related to the increase in temperature in DKI Jakarta's urban areas. Considering the potential of providing green open space can help form more accurate spatial policies in order to encourage control instruments over land use change, especially in the Detailed Spatial Planning of DKI Jakarta.